Soil Degradation in Salty Areas of Mid-Anatolia Region, Turkey¶ - IRMAK, S.; BALTA, C.; CARKACI, D.A.; GUNDOGAN, R. (Asian Journal of Chemistry, 2010)
The chemical, physical and morphological properties of six typical quaternary soil in the Kizilirmak plain of Çankiri and in the closed Lake Basin of Kayseri in the Mid-Anatolia region were investigated to determine salinity problem. The most important pedogenic prosses is salt translocation and accumulation in these soils. The salty underground water have influenced the chemistry and morphology of soils. The extensive salt crystals were observed in the A horizons of soils. A salic horizon were developed in the surface as a result of salt accumulation. The soluble salt contents of soils change between 0.46 and 3.05 %. Existence of extensive salt crystals in the soils in study area may be attributed to salty underground water and minerals. The high Na+ and Cl– content in the A horizon are related with salt accumulation. Exchangeable Ca2+ and Mg2+ account for > 95 % of the exchangeable complex as a result of dissolution of carbonates and possible weathering of feldspar.